2013
DOI: 10.1530/eje-13-0242
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane levels predict the outcome of patients with adrenocortical carcinoma treated adjuvantly following radical resection

Abstract: Context: Mitotane plasma concentrations R14 mg/l have been shown to predict tumor response and better survival in patients with advanced adrenocortical carcinoma (ACC). A correlation between mitotane concentrations and patient outcome has not been demonstrated in an adjuvant setting. Objective: To compare recurrence-free survival (RFS) in patients who reached and maintained mitotane concentrations R14 mg/l vs patients who did not. Design and setting: Retrospective analysis at six referral European centers. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 32 publications
(47 reference statements)
4
110
0
8
Order By: Relevance
“…Expectative management after successful surgery seems to be adequate in patients with localized disease and/or a low Wieneke index, which applies to all patients aged ≤4 years at diagnosis in our study. In adult patients, adjuvant treatment with mitotane is currently being evaluated prospectively, while retrospective studies suggest it is indicated in patients with a Ki-67 index >10% (23,24). based on our data, it is not possible to make recommendations for patients with a high Wieneke index and age ≥5 years.…”
Section: Authors ----------------------------------Hormonalmentioning
confidence: 87%
“…Expectative management after successful surgery seems to be adequate in patients with localized disease and/or a low Wieneke index, which applies to all patients aged ≤4 years at diagnosis in our study. In adult patients, adjuvant treatment with mitotane is currently being evaluated prospectively, while retrospective studies suggest it is indicated in patients with a Ki-67 index >10% (23,24). based on our data, it is not possible to make recommendations for patients with a high Wieneke index and age ≥5 years.…”
Section: Authors ----------------------------------Hormonalmentioning
confidence: 87%
“…3; Terzolo & Berruti 2008, Hermsen et al 2011, Terzolo et al 2013. Kerkhofs et al (2013c), who investigated the optimal dosing strategy, showed that 50% (10/20) of patients from the high dose starting regimen and 33% (4/12) of patients from the low-dose regimen reached the therapeutic level within 3 months.…”
Section: Current Therapeutic Strategiesmentioning
confidence: 99%
“…Monitoring the drug level (therapeutic levels of 14-20 mg/L) is highly important, because a good response to the treatment depends heavily on the drug serum levels [48,49]. In a long term study of patients with regional and metastatic ACC, scientists showed that the levels of o,p'-DDE (mitotane metabolite) were more closely related to clinical improvement or remission than o,p'-DDD levels (1,1-(dichlorophenyl)-2,2-dichloroethane; mitotane) [42].…”
Section: When To Use Mitotane?mentioning
confidence: 99%
“…W badaniach kontrolnych nadmierne wydzielanie hormonów występuje u 70-75% pacjentów. Monitorowanie stężenia leku (referencyjne wartości terapeutyczne wynoszą 14-20 mg/l) jest niezwykle istotne, ponieważ dobra odpowiedź na leczenie jest zależna od poziomu stężenia leku w osoczu [48,49].…”
Section: Patogeneza I Aspekty Molekularneunclassified